Wear performance under dry and lubricated conditions of duplex treatment TiN/TiCrN coatings deposited with different numbers of CrN interlayers on steel substrates - SALMAN, SERDAR (My University, 2023)
Cold work steels are used in harsh conditions including high load, wear, corrosion, and mechanical stresses that can easily lead to degradation and wear of the material. Generally, multilayer ceramics coatings are attractive candidates to develop engineering components by combining positive characteristics of different coatings. In this study, the TiN/TiCrN coatings with the different number of CrN interlayers were successfully deposited on nitrided and non-nitrided DIN 1.2379 steel, and their wear behavior was investigated at dry and lubrication conditions under different loads. The relationship between coating architectures and coating characteristics was explored. The microstructure and composition of the specimens were studied using X-ray diffraction (XRD), scanning electron microscopy (SEM) with Energy dispersive X-ray analysis (EDX) and Atomic force microscopy (AFM).The nano-hardness were measured by nanoindenter, respectively. The adhesion and tribological behavior were evaluated using the Rockwell-C indentation and reciprocating tribometer tests, respectively. The results reveal that the nitrided samples with the TiN/TiCrN coatings with the different number of CrN interlayer showed much better wear resistance than the non-nitrided coatings at dry conditions. On the other hand, nitrided and nitride + coated TiN/TiCrN with the different number of CrN interlayer specimen showed better wear resistance at lubricated conditions. In addition, the fact that uncoated and nitrided steels have higher wear resistance at lubricated conditions than coated samples shows that TiN/TiCrN coatings are not proper even with a lubricant additive over a certain load value.
Keywords: Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Kimya; Fizikokimya; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Chemistry; Physical Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; MALZEME BİLİMİ, KOMPOZİTLER; KİMYA, FİZİKSEL; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; FİZİK, YOĞUN MADDE; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; PHYSICS; MATERIALS SCIENCE, COMPOSITES; CHEMISTRY, PHYSICAL; MATERIALS SCIENCE, MULTIDISCIPLINARY; PHYSICS, CONDENSED MATTER; Yoğun Madde Fiziği; Fizik Bilimleri; Malzemelerin mekaniği; Yüzeyler ve Arayüzler; Yüzeyler, Kaplamalar ve Filmler; Malzeme Kimyası; Condensed Matter Physics; Physical Sciences; Mechanics of Materials; Surfaces and Interfaces; Surfaces, Coatings and Films; Materials Chemistry; arc-PVD coatings; Duplex surface treatment; Multilayer coatings; TiN/TiCrN coatings; Wear mechanisms; ZDDP anti-Wear additive; Duplex surface treatment; arc-PVD coatings; Multilayer coatings; TiN/TiCrN coatings; Wear mechanisms; ZDDP anti-Wear additive